Design of A Backstepping Control and Synergetic Control for An Interconnected Twin-Tanks System: A Comparative Study - Al-Majeez, Rawaa; Al-Badri, Kareem; Al-Khazraji, Huthaifa; Ra'afat, Safanah M. (Association for Scientific Computing Electronics and Engineering (ASCEE), 2024)
This paper presents a comparative performance examination between designing backstepping control (BSC) and synergetic control (SC) for an interconnected twin-tanks system. The controller is used to maintain the liquid level in the tank at the desired value by manipulating the input flow rate. The nonlinear dynamics of the twin-tanks system is established first. Then, based on the nonlinear dynamics of the system, the control law of the BSC and the SC are developed. The two controllers cooperate with the grasshopper optimization algorithm (GOA) for further improvement of the control design performance by tuning the design parameters of each controller. GOA has strong searchability for optimal solution and it has been successfully used to solve several optimization problems in numerous ï¬elds. Finally, the performance and the signiï¬cance of each controlled system for two case studies (normal operation and under external disturbance) are examined based on MATLAB software. The simulation data shows that the BSC gives better performance than the SC.